Fine artists' entrepreneurial business environment - Marco Thom (Institut für Mittelstandsforschung (IfM) Bonn, 2016)
This paper aims to illustrate the working and business environment of professional fine artists and to identify the factors to successfully make a living in the arts as both market challenges and success factors have not yet been clearly identified in literature. The identification of artists' business environment and success factors could be particularly beneficial for practising fine artists, prospective fine art students, and higher education institutions (HEIs) in order to provide them with a deeper market insight and knowledge for an effective professional education and preparation. In order to achieve this aim, the paper is first focused on the literature to identify working fine artists' business environment including the different art market segments, entry barriers, and challenges. In a second step, interviews with professional fine artists were conducted as well as surveys distributed to lecturers and students in Fine Art at HEIs and to galleries to determine the challenges and success factors in the art market from their professional experience. The literature and survey findings clearly show that the art market is characterised by different segments of varying market attention and visibility, whose access is controlled by informal market barriers consisting of powerful networks. The vast majority of fine artists are practising in segments excluded from buyers' awareness. – – Diese Paper hat das Ziel, das Arbeiten und die Geschäftsumgebung von professionellen Berufskünstlern zu illustrieren und die Faktoren zu identifizieren, um ein Leben im künstlerischen Bereich erfolgreich zu leben, weil sowohl Herausforderungen des Marktes als auch Erfolgsfaktoren noch nicht klar in der Literatur identifiziert worden sind. Die Identifizierung der Geschäftsumgebung und Erfolgsfaktoren von Künstlern kann besonders für zukünftige Studenten der bildenden Kunst und Hochschuleinrichtungen / Kunstakadiemien (HEI's), um sie dann mit einer tieferen Marktscharfsinnigkeit und Kenntnissen für eine wirksame Berufsausbildung zu versorgen. Um dieses Ziel zu erreichen, wird das Paper zunächst auf die Literatur eingehen, um die Arbeitsumgebung der Künstler, einschließlich der verschiedenen Kunstmarktsegmente, Zugangsbarrieren und Herausforderungen, zu identifizieren. Im zweiten Schritt wurden Interviews mit Berufskünstlern geführt sowie Umfragen an Dozenten und Studenten der bildenden Kunst an Hochschuleinrichtungen und Gallerien verteilt, um die Herausforderungen und Erfolgsfaktoren des Kunstmarktes von ihrer Berufserfahrung zu bestimmen. Die Ergebnisse der Literatur sowie den Umfragen, zeigen deutlich, dass der Kunstmarkt durch verschiedene Segmente der unterschiedlichen Marktaufmerksamkeit und Sichtbarkeit charakterisiert wird, deren Zugang von informellen Marktbarrieren kontrolliert wird, die aus starken Netzwerken bestehen. Die große Mehrheit von Künstlern üben ihren Beruf außerhalb des Bewusstseins des Käufers aus.
Keywords: A22; A23; 330; fine artists; success factors; business environment; art market segments; market barriers